HIKAYAT NABI MIKRAJ: SEBUAH ANALISIS INTERTEKSTUAL - Abdul Lathif; Asep Yudha Wirajaya (tuahtalino, 2020)
The purpose of this study was to determine the intertextuality relationship of the text of the Story of the Prophet Mikraj with the Sahih Bukhori Hadith about isra mikraj. The spiritual story of isra mikraj is a very sacred story for Muslims. Even today many writings still discuss the sacred event from various perspectives. Similarly, the ancients have perpetuated the story in a variety of writings, including in the form of story prose. Of course, the writing is sourced from the story of isra mikraj contained in muthatith hadith texts, such as Sahih Bukhari, Sahih Muslim, Sunan at Tirmidzi, and so forth. One ancient text that was successfully preserved was the Hikayat Nabi Mikraj. This manuscript contains a text about the events of the Prophet Muhammad SAW. Thus, it can be assumed that the existence of the text of the Hikayat Nabi Mikraj cannot be separated from the previous texts, namely the text contained in the muthatith Hadith.